DEVELOPING BLENDED LEARNING BASED READING MATERIALS FOR THE TENTH GRADE MULTIMEDIA STUDENTS OF SMK WIRA HARAPAN - Meliawati, .Komang (Jurnal Pendidikan dan Pembelajaran Bahasa Indonesia, 2018)
This study was a research and development (R&D) study designed by Lee and Owens (2004) which involved: need analysis, design, development, implementation, and evaluation. The data were gathered through observation, questionnaires, interview, validation technique and test. The method of data collections were interactive data analysis and ideal theoretic reference. The result of this study showed that: (1) the students need specific reading material based on their future job; (2) the design of Blended Learning whose purpose was to make the teaching and learning process became student- centered activity and makes the students become self-assisted language learners; (3) the developed blended learning based on reading material had a very high validity; (4) the developed blended learning based on reading material could improve the students? reading comprehension; and (5) In developing and implementing the blended learning based reading material,  the technical problem was faced by the teacher.